2017
DOI: 10.1007/s10886-017-0906-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mixture Designs to Investigate Contribution of Minor Sex Pheromone Components to Trap Catch of the Carpenterworm Moth, Chilecomadia valdiviana

Abstract: Field experiments were carried out to study responses of male moths of the carpenterworm, Chilecomadia valdiviana (Lepidoptera: Cossidae), a pest of tree and fruit crops in Chile, to five compounds previously identified from the pheromone glands of females. Previously, attraction of males to the major component, (7Z,10Z)-7,10-hexadecadienal, was clearly demonstrated while the role of the minor components was uncertain due to the use of an experimental design that left large portions of the design space unexplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…2) As a result of the discovery of Z6,Z9-22:H (30) and Z3,Z6,Z9-22:H (33) from an Arctiinae species in Erebidae, the 6,9-dienes with a C 19 -C 22 chain and the 3,6,9-trienes with a C 17 -C 23 chain have become recognized as natural pheromone components. Z6,Z9-21:11-OH (31) and Z6,Z9-21:11-one (32) are new pheromone components found from three Lymantriinae species. One of them also secretes corresponding common Type II compounds, Z6,Z9-21:H and Z6,epo9-21:H. Although the biosynthesis of the new compounds from linoleic acid has not been experimentally proven, the dienyl structure suggests their production by enzymatic oxidation at the allylic 11-position of the 6,9-diene.…”
Section: Structures Of New Pheromones In Type IImentioning
confidence: 89%
See 1 more Smart Citation
“…2) As a result of the discovery of Z6,Z9-22:H (30) and Z3,Z6,Z9-22:H (33) from an Arctiinae species in Erebidae, the 6,9-dienes with a C 19 -C 22 chain and the 3,6,9-trienes with a C 17 -C 23 chain have become recognized as natural pheromone components. Z6,Z9-21:11-OH (31) and Z6,Z9-21:11-one (32) are new pheromone components found from three Lymantriinae species. One of them also secretes corresponding common Type II compounds, Z6,Z9-21:H and Z6,epo9-21:H. Although the biosynthesis of the new compounds from linoleic acid has not been experimentally proven, the dienyl structure suggests their production by enzymatic oxidation at the allylic 11-position of the 6,9-diene.…”
Section: Structures Of New Pheromones In Type IImentioning
confidence: 89%
“…The pathways of (C) and (E) are putative. (32), acids and derivatives (34), and ring comp. (27) for methylbranched nonterpene compounds (total 201); acyclic comp.…”
Section: Database Of Arthropod Semiochemicalsmentioning
confidence: 99%
“…The pheromone lures for the trap type and trap height experiments were prepared by loading white rubber septa (Sigma-Aldrich, catalog #Z553905) with 100 µL of a hexane solution containing 300 µg of synthetic Z7,Z10-16:Ald, which was synthesized by Shin-Etzu Chimical Co, Ltd. (Tokyo, Japan), as described previously in Lapointe et al [12].…”
Section: Preparation Of Luresmentioning
confidence: 99%
“…The major pheromone component is (7Z,10Z)-7,10-hexadecadienal (Z7,Z10-16:Ald) and the minor compounds are (Z)-7-hexadecenal, (Z)-9-hexadecenal, hexadecanal, and (9Z,12Z)-9,12octadecadienal [11]. Later studies demonstrated that the minor compounds do not enhance long-range male attraction over Z7,Z10-16:Ald alone [12]. Knowledge of the pheromone of this moth opens possibilities for its sustainable management through flight monitoring, mating disruption, or mass trapping [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides direct and indirect damage to the tree, the presence of C. valdiviana also affects export of wood products because of quarantine restrictions in destination countries [14]. The main pheromone component produced by females is the unsaturated aldehyde (7Z,10Z)-7,10hexadecadienal (Z7,Z10-16:Ald), together with small amounts of structurally related compounds [15], and it was shown that the Z7,Z10-16:Ald alone is responsible for the long-range attraction of males to the pheromone source [16]. Because aldehydes are susceptible to degradation, particularly under field conditions, and the degradation products are usually not biologically active, we synthesized an analog, (5Z,8Z)-5,8-tetradecadienyl formate (Z5,Z8-14:Fo), in which the α-methylene group is formally replaced by an oxygen atom (Fig.…”
Section: Introductionmentioning
confidence: 99%